IMPACT OF FOREST ON WATER ENVIRONMENT - Khudonazarov А.С. (Hydrometeorology and ecology, 2023)
The influence of forests on water ecosystem is examined. The influence of afforestation and deforestation on river runoff from small catchment basins, the influence of forests on the annual runoff of rivers and on quality of fresh water have been studied. Conclusions are given for each of the studied sections.